Antifungal metabolite profiling in Chaetomium globosum potential strain Cg2 effective against Bipolaris sorokiniana - K, DARSHAN; AGGARWAL, RASHMI; BASHYAL, BISHNU MAYA; SINGH, JAGMOHAN; KUNDU, ADITI; YADAV, SURESH; SAHARAN, M S (The Indian Journal of Agricultural Sciences, 2021)
The fungus reported to be a potential antagonist of various soil and seed borne plant pathogens. C. globosum mycoparasitizes and produce antifungal metabolites which suppress the growth of the pathogenic fungi. Despite sufficient knowledge available on secondary metabolites of C. globosum and their wide biological activities, limited literatures are available on the polar active constituents and their potential use as antifungal agent. The study was carried out to evaluate chemical composition of secondary metabolites from C. globosum when it interacts with Bipolaris sorokiniana (2017-2020). The volatile compounds identified through GC-MS revealed that, C. globosum strain Cg2 produced a variety of antifungal secondary metabolites, i.e. octadecene trans-limonene oxide, dodecane, tetracosonal, heptacosanol and octadecanoic acid which may be involved in the antagonism. Similarly, UPLC-QToF-ESIMS analysis of chloroform soluble fraction of C. globosum (Cg2), B. sorokiniana (BS112) and their interaction (Cg2-BS112) were undertaken to identify non-volatile metabolites.These metabolites were identified as Chaetomugilin A, D, E, F, Globoxanthone A, Chaetoviridin A, B, E, Chaetoglobin B, Chaetoquadrin A, Chaetocochin B and F, Chaetoglobosin Q and N.The work indicates that the biocontrol agent C. globosum showed high antifungal metabolite production thereby antagonising B. sorokininana pathogen. The obtained data will greatly enrich current C. globosum metabolomic information and provide a good foundation for better understanding of biocontrol mechanism of C. globosum against plant pathogens and facilitating widespread application in the field of bio-control.